2016
DOI: 10.1097/md.0000000000002606
|View full text |Cite
|
Sign up to set email alerts
|

Severe Infection With Avian Influenza A Virus is Associated With Delayed Immune Recovery in Survivors

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…These observations confirmed the data reported by other studies where ECM pathways were significantly down-regulated in HPAI H7N9 and HPAI H5N1 [43]. A separate report also described that in human survivors of severe H7N9 infection, related proteins from the hydrolysis of fibronectin and collagens IV were found present in their plasma, suggesting that the ECM pathway was actively involved in remodeling damaged tissues [44].…”
Section: Discussionsupporting
confidence: 91%
“…These observations confirmed the data reported by other studies where ECM pathways were significantly down-regulated in HPAI H7N9 and HPAI H5N1 [43]. A separate report also described that in human survivors of severe H7N9 infection, related proteins from the hydrolysis of fibronectin and collagens IV were found present in their plasma, suggesting that the ECM pathway was actively involved in remodeling damaged tissues [44].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Chen, Zhou [ 22 ] also reported that EMC pathway was involved in H7N9 infection. On the other hand, Chen, Cui [ 23 ] found that higher plasma levels of hydrolysis of fibronectin and collagens IV related proteins in survivors of severe H7N9 infection and they hinted the ongoing tissue remodeling after severe H7N9 infection. Thus, the perturbed extracellular matrix pathway in cells might also hint the damaged tissue remodeling of cells, which devastated the fatality.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that persistent abnormal MDSCs, including G-MDSCs and M-MDSCs, may be accompanied by a persistent state of “immunoparalysis”. Chen et al reported that in severe H7N9 patients, the total lymphocyte count and percentages of different lymphocyte subtypes returned to normal levels 1 month post-infection, while 3 months were needed for the normalization of CD14 + HLA-DR lo/neg MDSCs [ 30 ]. Unfortunately, our study did not record when the CD14 + HLA-DR lo/neg MDSC frequency of COVID-19 patients returned to normal levels.…”
Section: Discussionmentioning
confidence: 99%